ANALISIS BEBAN KERJA UNTUK MENENTUKAN JUMLAH OPTIMAL OPERATOR PADA BAGIAN PROSES PABRIK KELAPA SAWIT (Studi Kasus: PT. Sentosa Kalimantan Jaya) - Marsidi; Rusli Anwar; Rossy Mirasari (JURNAL AGRIMENT, 2020)
This research is motivated by the difficulty in determining the optimal number of human resources required. To be able to calculate HR requirements accurately, a device called a Workload Analysis (ABK) is needed. This study aims to analyze the operator's job description, an overview of the use of operator working time, and workload and needs. The method used is job description analysis, calculation of productive work time usage with work sampling method, and workload analysis using Full Time Equivalent (FTE) method based on work unit activity. The results of the workload analysis show that there are job descriptions that have not been listed in the written description of the company and there are still stations that have a written job description that does not match the work in the field. The percentage of productive working time for operators is between 42% and 77%, all of which are still low because they are below the standards set by the company, which is 85%. Calculation of the workload of the process part operator, obtained an FTE figure of 7.6 which means the optimal number of operators required by the process section is 8 people. This number is in accordance with the actual number in the process section, namely 8 people.